The association between IL-1RA gene, TNF-beta gene, TNF-alpha gene, IL-4 gene and IFN-gamma gene with graves disease in Thai - Jeerawat Nakkuntod (Chulalongkorn University, 2008)
Thesis (M.Sc.)--Chulalongkorn University, 2003